Media Pengembangan Bakat Dan Ketrampilan Santri Pondok Pesantren Nur Fadhilah Dalam Pengoptimalan Sumber Daya Manusia - Nurcahyo, Mugi (Journal of Community Development and Disaster Management, 2021)
Absract : empowerment of students and youth in a boarding school that is in the midst of society as an effort to develop human resources in fields that may someday students already be in the community. The reason for the HR development program being implemented in this Islamic boarding school is to remember the human resources that are owned or the potential that is in vain at a young age who should have gained experience as a provision for the next life which is now being replaced with things that are not important. For this reason, this Islamic boarding school implements the program. The approach or research method used in the empowerment is education carried out by Islamic boarding schools to students and youth through skills training and social sciences. The result of this program is to train local students and youth, apart from getting knowledge of the Islamic boarding school, they also get provisions which can then be applied in their respective communities. Keywords: empowerment of youth and students, islamic boarding schools Nur Fadhilah Abstrak : pemberdayaan santri dan pemuda di dalam sebuah pondok pesantren yang berada di tengah masyarakat sebagai upaya dalam mengembangkan SDM pada bidang yang mungkin nanti kelak santri sudah berada di masyarakat. Program pengembangan SDM yang diterapkan di pondok pesantren ini, yaitu mengingat SDM yang di miliki atau potensi yang sia-sia di usia muda yang harusnya sudah mendapat pengalaman untuk bekal masa depan terganti dengan hal yang kurang penting, untuk itu pondok pesantren ini menerapkan program tersebut. Pendekatan atau metode penelitian yang di gunakan dalam pemberdayaan tersebut ialah edukasi yang di lakukan oleh pondok pesantren kepada santri dan pemuda melalui pelatihan ketrampilan dan ilmu sosial. Hasil dari program ini adalah untuk melatih santri dan pemuda setempat selain mendapat ilmu pengetahuan pondok, mereka juga mendapat bekal ilmu dan pengalaman yang kemudian dapat mengaplikasikanya di masyarakat masing-masing. Kata kunci : pemberdayaan pemuda dan santri, pondok pesantren Nur Fadhilah